2021
DOI: 10.1590/1518-8345.4964.3481
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care in Mozambique: Number of visits and gestational age at the beginning of antenatal care

Abstract: Objective: 1)to assess the gestational age at the beginning of antenatal care and its covariates; 2)to assess the number of antenatal visits and its covariates; and 3)to identify the reasons for the late initiation of antenatal care and for attending less than four visits among postpartum women living in Nampula, Mozambique. Method: cross-sectional study conducted with 393 mothers who answered a structured instrument in face-to-face interviews. Logistic regression was used to analyze the covariates of having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Based on an analysis of 10 primary studies, it was found that mothers with higher education were 2.93 times more likely to take advantage of antenatal care than mothers with low education (aOR = 2.93; 95% CI = 1.93 to 4.45; p = 0.001). This is in line with Reis-Muleva et al (2021) which revealed that mothers with higher education were 2.91 times more likely to utilize antenatal services compared to mothers with low education.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on an analysis of 10 primary studies, it was found that mothers with higher education were 2.93 times more likely to take advantage of antenatal care than mothers with low education (aOR = 2.93; 95% CI = 1.93 to 4.45; p = 0.001). This is in line with Reis-Muleva et al (2021) which revealed that mothers with higher education were 2.91 times more likely to utilize antenatal services compared to mothers with low education.…”
Section: Discussionsupporting
confidence: 89%
“…Efforts to plan a pregnancy are made so that the 4Ts do not occur, namely Too Young, Too Old, Too Often, and Too Many. Based on research in Mozambique, 47.5% of those who used antenatal care did not plan a pregnancy, while 55.9% did not plan a pregnancy (Reis-Muleva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some women may have attended their first ANC visit at >6 months' gestation and therefore did not reach retesting eligibility during pregnancy. However, in a 2019 study conducted in Nampula, 40% of pregnant women attended their first ANC visit by 16 weeks [17] indicating that most women tested at the first ANC visit should have had a least one additional ANC visit prior to delivery where they could have received retesting.…”
Section: Plos Onementioning
confidence: 99%
“…Only 34.1% of women start antenatal consultations before the 16th gestational week and attend at least 4 visits; moreover, they report lack of easy access to the health facility as one of the reasons for late initiation of antenatal care. (23) However, progress in utilisation of antenatal services has been made since equipment and supplies. As part of their training, they learned how to prioritise health care and how to recruit community volunteers to help run the unit.…”
Section: Care In Mozambiquementioning
confidence: 99%